2016
DOI: 10.1177/0885066616675130
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Reintubation After Unplanned Extubations in Children: Art or Science?

Abstract: The rate of reintubation is high in children experiencing UE. Requirement of full ventilator support and a COMFORT score <26 are associated with reintubation. Prospective research is required to better understand the reintubation decisions and needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Furthermore, in a single-center case-control study of patients undergoing general surgical procedures, Rujirojindakul et al 20 reported that infants had a roughly 16-fold higher risk of UPI than young adults. In addition, da Silva et al 11 found that re-intubation rates in infants in the ICU (for surgical and nonsurgical conditions) were much higher than in children of other ages. While these studies all differ across a variety of patient demographics, study designs, surgical specialties, and even nonsurgical ICU patients, they all support our finding that young age places children at significantly increased risk for UPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a single-center case-control study of patients undergoing general surgical procedures, Rujirojindakul et al 20 reported that infants had a roughly 16-fold higher risk of UPI than young adults. In addition, da Silva et al 11 found that re-intubation rates in infants in the ICU (for surgical and nonsurgical conditions) were much higher than in children of other ages. While these studies all differ across a variety of patient demographics, study designs, surgical specialties, and even nonsurgical ICU patients, they all support our finding that young age places children at significantly increased risk for UPI.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies exploring the incidence and risk factors for unplanned postoperative intubation (UPI) were conducted in adult patients and are not specific to neurosurgical procedures 5–9 . Few pediatric studies have focused on children admitted to the ICU for various conditions (respiratory disorders, sepsis, trauma, and others) or on children undergoing cardiac surgery 10–13 . These patients have unique characteristics that limit the generalizability of these studies to specific patients presenting for craniotomy.…”
mentioning
confidence: 99%
“…Flexible bronchoscopy is becoming a more popular than rigid bronchoscopy to remove FBs [ 4 , 5 ]. Reintubation is a severe complication occurring in both flexible bronchoscopy and rigid bronchoscopy [ 6 ]. Reintubations lead to prolonged mechanical ventilator support, increased postoperative ICU admission, and a higher cost [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reintubation is a severe complication occurring in both flexible bronchoscopy and rigid bronchoscopy [ 6 ]. Reintubations lead to prolonged mechanical ventilator support, increased postoperative ICU admission, and a higher cost [ 6 ]. Identifying and focusing on children with higher risks of reintubations are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned extubations in pediatric critical care require emergent, critical attention from clinicians to assess and support the patient’s respiration and ventilation. Reintubations after an unplanned extubation are associated with a higher risk of complications and a lower probability of success, when compared with a planned intubation in a controlled environment (1). Inserting the breathing tube multiple times increases the risk of airway injury, causing inflammation to the oropharynx or nasopharynx, larynx and trachea (2).…”
mentioning
confidence: 99%